MODEL VALUE CLARIFICATION TECHNIQUE PADA PENDIDIKAN BIDAN DALAM MEWUJUDKAN PENDIDIKAN INDONESIA EMAS 2045 - Handayani, Dini Saraswati (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
The implementation of character education is the duty and responsibility of educational institutions, in accordance with applicable laws and regulations and demands in the era of globalization. In addition, the role of educators, academic staff and institutions has an important role in developing methods for implementing character education in higher education. So that what is expected by the government regarding the outcomes of higher education institutions that have strong knowledge and character is realized. The government holds the hope that every graduate from higher education will have the ability to develop character and knowledge well. However, what has happened recently, is very different from the expected expectations. This phenomenological analysis hopes to provide an overview regarding the development of the value clarification technique (VCT) model in midwife education. So that the six main characters can be applied to midwife education, especially the characters of respect, respect, fairness, caring, and citizenship. Because some of the research results related to the VCT model turned out to be able to increase the value possessed by students at the primary and secondary education level. Therefore, the contribution of this paper is in efforts to develop a VCT model in higher education, in realizing the golden generation in 2045.